Evaluation studies of headspace BOD technique - Kumar, Madhav (My University, 2013)
Headspace BOD (HBOD) tests was developed that avoided the need to diluted wastewater samples. The main advantage of HBOD test is that the test can be performed more easily than the BOD test because no sample dilutions are necessary, the oxygen demand can be determined within a shorter period of time (24- 36 hours) can provide an accurate prediction of the 5 day value and the experimental conditions used in the HBOD test more accurately reproduce the hydro-dynamic and culture conditions typical of wastewater treatment bioreactor. Characterization of waste water is very important in the selection of appropriate effluent treatment systems and in the design of constituent treatment units of such systems. Since biodegradable organic matter is an important parameter, such characterization requires inclusion of biodegradable organic matter as one of the parameters of characterization. From the review of literature it is observed that conventional biochemical oxygen demand BOD test requires a series of sample dilution because usually wastewater contains high concentration of organic matter, while concentration beyond 7mg/l can-not be tested by this method. Dilution of the sample is the main cause for introduction of error into the BOD measurement by considering these factors other alternative techniques have been developed like respirometric technique, bio-sensor methods and headspace methods. Respirometric BOD test procedures are now included in the standard methods as proposed method. Respirometric methods are routinely used in Europe.
Master of Technology Environmental Science and Technology)
Keywords: BOD; DO; wastewater